If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 = 60 + v Solving 70 = 60 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 70 + -1v = 60 + v + -1v Combine like terms: v + -1v = 0 70 + -1v = 60 + 0 70 + -1v = 60 Add '-70' to each side of the equation. 70 + -70 + -1v = 60 + -70 Combine like terms: 70 + -70 = 0 0 + -1v = 60 + -70 -1v = 60 + -70 Combine like terms: 60 + -70 = -10 -1v = -10 Divide each side by '-1'. v = 10 Simplifying v = 10
| 2=6x^5 | | 6x+8y=6 | | 3(4x-2)=7(x+2) | | m^2+7m-30=0 | | 20=o-3 | | m^2+7n-30=0 | | 8y=28-4x | | 360=x+2(x-2) | | 4x+8=-55-5x | | 20x^2+8xy=0 | | (X^3)-(2x^2)-(x)-1=0 | | 75-9g=5(4+2g) | | 11d=24+8d | | 3x-6x=-3 | | 450=100(3)+b | | 1y+2x=15 | | 74x=100. | | 3x+5=7x-18 | | 3x+38+55=180 | | 5y+6x-2=0 | | 12x^2-17x-7= | | 2x+3=146 | | 7v+2=8 | | 2(3x+5)=6x-4 | | 7y=9-(4Y) | | 21x^6-35x^9= | | (2x+4)+(x+1)=3(x-1)+7 | | -2-2x=5x+79 | | 1.6x+10.6=3.3x-3 | | X=x^2-8x+12 | | 1.6x+10.6=3.3-3 | | 8-5x=-6x+16 |